Pseudomonas aegrilactucae sp. nov. and Pseudomonas morbosilactucae sp. nov., pathogens causing bacterial rot of lettuce in Japan. Issue 11 (4th November 2022) - Sawada, Hiroyuki; Fujikawa, Takashi; Satou, Mamoru
Abstract : Phytopathogenic bacterial strains (MAFF 301350 T, MAFF 302030 T and MAFF 302046), isolated from lettuce ( Lactuca sativa var. capitata ) with bacterial rot disease in Japan, were subjected to polyphasic characterization to determine their taxonomic affiliations. The cells were Gram-reaction-negative, aerobic, non-spore-forming, motile with polar flagella and rod-shaped. The results of similarity searches and phylogenetic analyses based on the 16S rRNA gene sequences, as well as the analysis results of the cellular fatty acid composition and genomic DNA G+C content indicated that these strains belong to the genus Pseudomonas . Phylogenetic analyses using the rpoD gene sequences and phylogenomic analyses of the whole genome sequences grouped them into the Pseudomonas putida group (MAFF 301350 T ) and the Pseudomonas fluorescens group (MAFF 302030 T and MAFF 302046), but the phylogenetic positions of the strains did not match those of any known Pseudomonas species. The average nucleotide identity and digital DNA–DNA hybridization values between the strains and their closely related species were lower than the thresholds for prokaryotic species delineation (95–96 and 70 %, respectively). Phenotypic characteristics, pathogenicity toward lettuce, cellular fatty acid composition and whole-cell MALDI-TOF mass spectrometry profiles could differentiate the strains from their closest relatives. The phenotypic, chemotaxonomic and genotypic data obtained in this study showed that the strains represent two novel species of the genus Pseudomonas, Pseudomonas aegrilactucae sp. nov. for MAFF 301350 T and Pseudomonas morbosilactucae sp. nov. for MAFF 302030 T and MAFF 302046. The respective type strains are MAFF 301350 T (= ICMP 23989 T ) and MAFF 302030 T (= ICMP 24377 T ).